Republic of Armenia : 2010 Article IV Consultation, First Review Under the Extended Financing Facility and Extended Credit Facility, and Request for Modification of Performance Criteria-Staff Report; Public Information Notice and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2010)
The Armenian economy suffered a major setback during the global crisis. Recent macroeconomic developments are encouraging, despite inflation pressures. The fiscal policy strategy appropriately addresses medium-term fiscal and debt vulnerabilities. The monetary policy has been appropriate. The increased flexibility of the exchange rate is serving well, and the banking sector remains sound and proved resilient to the global shocks. Further improvement in tax administration is needed to support fiscal consolidation and achieve stronger growth. Structural reforms will be essential to enhance competitiveness.